Practitioner review: Treatments for Tourette syndrome in children and young people: a systematic review - Whittington, Craig; Pennant, Mary; Kendall, Tim; Glazebrook, Cris; Trayner, Penny; Groom, Madeleine J.; Hedderly, Tammy; Heyman, Isobel; Jackson, Georgina M.; Murphy, Tara; Rickards, Hugh; Robertson, Mary; et al. (Wiley, 2016)
Background: Tourette syndrome (TS) and chronic tic disorder (CTD) affect 1–2% of children and young people, but the most effective treatment is unclear. To establish the current evidence base, we conducted a systematic review of interventions for children and young people.